2006
DOI: 10.1097/01.jsm.0000244610.34594.07
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability, Blood Pressure Variability, and Baroreflex Sensitivity in Overtrained Athletes

Abstract: Abruptly intensified physical training results in an altered autonomic cardiovascular activity towards parasympathetic inhibition and sympathetic activation that can be monitored by means of HRV and BRS analyses and might provide useful markers to avoid the overtraining syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 36 publications
6
72
1
8
Order By: Relevance
“…Differences in the results are probably due to differences in the exercise modes and intensities, length of the training period, and training status of the subjects. Non-functional overreaching or overtraining syndrome has usually been found to decrease resting HRV (Uusitalo et al 1996;Baumert et al 2006;Hynynen et al 2007;Pichot et al 2000). Studies that have reported increase in VO2max of more than 12 ml/kg/min after endurance training have also reported an increase in vagal control of the heart (Carter et al 2003).…”
Section: Hrv and Endurance Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the results are probably due to differences in the exercise modes and intensities, length of the training period, and training status of the subjects. Non-functional overreaching or overtraining syndrome has usually been found to decrease resting HRV (Uusitalo et al 1996;Baumert et al 2006;Hynynen et al 2007;Pichot et al 2000). Studies that have reported increase in VO2max of more than 12 ml/kg/min after endurance training have also reported an increase in vagal control of the heart (Carter et al 2003).…”
Section: Hrv and Endurance Trainingmentioning
confidence: 99%
“…HRV has been found to indicate fluctuations in the ANS during different conditions, such as rest, physical exercise, and daily activities (Akselrod et al 1985;Martinmäki et al 2006a;Task Force, 1996). Decreased levels of HRV have been found in overtrained athletes (Baumert et al 2006;Hynynen et al 2007; Uusitalo et al 1996) as well as in several diseases, e.g. increased risk for death after myocardial infarction .…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, estudos recentes em que as alterações das cargas de treinamento não foram tão grandes, não encontraram alterações na VFC após períodos com cargas de treinamento diferentes, moderadas e altas ao longo da temporada esportiva 16,17 . Sendo assim, mudanças na modulação autonômica cardíaca aparentemente são percebidas apenas em situações em que atletas são submetidos a cargas de treinamento extremamente elevadas, de forma a levar os voluntários à exaustão 9,15 , o que nem sempre ocorre numa situação real de treinamento com finalidade competitiva, como nesta investigação, na qual o programa de treinamento foi concebido visando a participação em competição de nível nacional, e, não, no intuito de levar os voluntários a situações extremas de fadiga crônica. Outros estudos mostram, ainda, que ocorrem modificações na atuação simpática apenas em períodos curtos de tempo como adaptação ao treinamento, imediatamente seguintes às alterações na carga de exercícios 13,14,17 .…”
Section: Estresse Geralunclassified
“…Entretanto, essa elevação nas exigências do treinamento pode não somente gerar adaptações positivas nos atletas e em seu desempenho, como também trazer prejuízos ao desportista quando o treinamento exceder a capacidade de regeneração individual, causando estagnação e/ou queda do rendimento e podendo levar a um quadro conhecido como "síndrome do excesso de treinamento" ou overtraining 1,2,4,5,7,8 . O overtraining é considerado um desequilíbrio entre as cargas de treinamento e a devida recuperação, capaz de regenerar o organismo 6 , assim como é o resultado de um desequilíbrio entre estresse e recuperação, no qual o estresse é resultado de fatores inter e extra-treinamento, como carga de treinamento, número excessivo de competições, frequentes viagens, lesões, dificuldades financeiras, conflitos pessoais e dificuldades de relacionamento (pais, amigos, familiares, técnicos) 6,9 . Pesquisas tentam identificar marcadores, possíveis indicadores fisiológicos e bioquímicos do estado de treinamento, tais como relação testosterona/cortisol, concentrações máximas de lactato, concentrações plasmáticas de catecolaminas, hemoglobina, creatina quinase 4,10-12 e o balanço simpáto-vagal, o qual tem sido constantemente investigado com a utilização da variabilidade da frequência cardíaca em atletas com overtraining e em treinamento, sob diferentes cargas de treinamento, devido à grande influência do treinamento sobre o controle autonômico cardíaco 9,[13][14][15][16][17] .…”
Section: Introductionunclassified
See 1 more Smart Citation